Atmospheric and river-derived mercury fluxes in distinct natural communities of a river delta - Goss, P.; Landis, J. D.; Wang, T.; Taylor, V. F. (Frontiers in Environmental Chemistry, 2025)
IntroductionRiver deltas play an important role in sequestering and storing mercury (Hg), restricting its release into downstream bodies of water. Delta landscapes encompass a patchwork of distinct wetland soils and vegetation, which accumulate Hg from both atmospheric and watersheds sources, and have varying capacities for long-term Hg retention.MethodsTo better understand Hg retention in the complex mosaic of delta soils, this study used soil age models based on fallout radionuclides (FRNs, 210Pb, 7Be, 241Am) to measure Hg flux to three distinct natural communities in the Missisquoi River Delta, Vermont.ResultsSoil profiles of radionuclide and Hg flux from a pitch pine bog, a silver maple floodplain forest, and a wild rice marsh all revealed long-term retention of Hg, despite varying susceptibilities to frequent hydrological disturbances. A mass balance approach was applied to apportion Hg fluxes to each region of the delta based on regional values of Hg wet deposition, measured FRN and Hg inventories, and measured or estimated foliar Hg inputs. Spaghnum peat soils of the pitch pine bog had the lowest Hg flux, consistent with uptake predominantly from wet deposition, while Hg accumulation doubled in bog soils developed under shrub or tree canopies, due to strong foliar and non-foliar uptake of gaseous elemental Hg (GEM). Soils in the silver maple floodplain received the highest Hg flux, driven by both GEM uptake and large riverine sedimentary inputs. Surprisingly, submerged soils in the wild rice marsh recorded substantially lower Hg flux than the adjacent silver maple forest, with low inputs of Hg from both GEM and watershed sources.ConclusionThis novel chronometry framework for elucidating pathways of Hg accumulation across distinct deltaic environments revealed the variable roles of vegetation type and flooding regime in controlling Hg inputs to delta soils.